2020
DOI: 10.7554/elife.53169
|View full text |Cite
|
Sign up to set email alerts
|

An ultralong CDRH2 in HCV neutralizing antibody demonstrates structural plasticity of antibodies against E2 glycoprotein

Abstract: A vaccine protective against diverse HCV variants is needed to control the HCV epidemic. Structures of E2 complexes with front layer-specific broadly neutralizing antibodies (bNAbs) isolated from HCV-infected individuals, revealed a disulfide bond-containing CDRH3 that adopts straight (individuals who clear infection) or bent (individuals with chronic infection) conformation. To investigate whether a straight versus bent disulfide bond-containing CDRH3 is specific to particular HCV-infected individuals, we sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Moreover, as well as stabilizing the protruding structure and directly altering the antigen contacts, SHM can generate local flexibility that allows the antigen-binding site to engage with its respective target at a variety of angles, significantly improving neutralization activity in some cases [16]. Although rare in human antibody genes, large nucleotide insertions (>40 nt) introduced by sequence duplication during the error-prone repair of SHM have been shown to contribute to antigen recognition [32]. Whilst the high SHM rate is not conducive to their induction via classical vaccination, it does not prevent the use of previously generated BNAbs therapeutically [33,34].…”
Section: The Long Cdr H3 Is Generated Inefficiently In Humansmentioning
confidence: 99%
“…Moreover, as well as stabilizing the protruding structure and directly altering the antigen contacts, SHM can generate local flexibility that allows the antigen-binding site to engage with its respective target at a variety of angles, significantly improving neutralization activity in some cases [16]. Although rare in human antibody genes, large nucleotide insertions (>40 nt) introduced by sequence duplication during the error-prone repair of SHM have been shown to contribute to antigen recognition [32]. Whilst the high SHM rate is not conducive to their induction via classical vaccination, it does not prevent the use of previously generated BNAbs therapeutically [33,34].…”
Section: The Long Cdr H3 Is Generated Inefficiently In Humansmentioning
confidence: 99%
“…They predominantly overlap with the binding site for CD81 that is composed of (1) a conserved N-terminal region (residues 412–423, epitope I), (2) a front layer region comprising of a short α-helix (aa428–446) and (3) an adjacent loop named CD81-binding loop (aa519–535). Structural characterization of bNAb fragments in a complex with soluble E2 ectodomains or ectodomain fragments revealed that a number of potent cross-neutralizing bnAbs—often derived from the VH 1-69 gene family—recognize a complex conformation-sensitive epitope, called complex “front layer epitope” (CFL) [ 43 , 44 , 45 , 46 ]. However, not all Abs targeting one of these epitopes neutralize HCV infection, although similar contact residues are employed [ 47 , 48 , 49 ].…”
Section: The E2 Glycoproteinmentioning
confidence: 99%
“…The igVR is not defined by electron density in the complex structures with the 2A12 Fab, in the AR3C Fab-E2 core complex structure it adopts a disulfide-constrained loop (C 569 -C 581 ) [ 43 ]. More recently, Flyak and coworkers described four structures of the full-length E2 ectodomain: three from genotype 1b complexed with Fab fragments of the bnAb HEPC3, HEPC76 and AR3X respectively, and one of a genotype 1a ectodomain engaged in a ternary complex with Fab fragments of the bnAbs HEPC46 and HEPC3 [ 44 , 46 ]. Although the four E2 ectodomain structures are derived from different strains, they are very similar in their core region and feature common disulfide bond connectivity [ 44 , 46 ] ( Table 1 ).…”
Section: The E2 Glycoproteinmentioning
confidence: 99%
See 2 more Smart Citations